التوجه بخصائص التحلیل الاقتصادي للرعایة الصحیة في التسویق الاجتماعي للخدمة الصحیة - لیتیم, خالد (Finance and Business Economies Review, 2018)
This study focus on trying to formulate a framework for the social marketing practices developed in the health care sector, according to the characteristics of the variables of the health marketing environment in this sector, and within the characteristics of economic analysis in healthcare In the context of this study, we showed that when the health sector is primarily related to the human aspect, it is natural to believe in ideas that positively reflect on the public interest by adopting comprehensive values to improve the health of the community as a whole rather than just clinical needs. By adapting marketing methods to use in public health campaigns to promote health awareness, and to seek to eliminate gaps between patients and the health establishment. The management of waiting lines that prevent the treatment of patients with quantitative entry, the responsibility to suppress the wishes of the patient, the need to change and rationalize health behavior; This extends to include pharmaceutical companies that must adopt the principles of social responsibility in their marketing practices to avoid monopoly, and research on the problem of neglected diseases. Although this sector has the low level of attractiveness